The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1161/strokeaha.107.506485
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Dural Arteriovenous Shunts

Abstract: Background and Purpose— Dural arteriovenous shunts with cortical venous reflux or drainage may cause neurological symptoms and death with or without intracranial hemorrhage. Present knowledge about the natural history of these lesions is limited, however. We investigated the incidences of intracranial hemorrhage, progressive dementia syndrome, and death in patients diagnosed in our neurovascular center. Methods— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
164
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(175 citation statements)
references
References 22 publications
(41 reference statements)
4
164
0
7
Order By: Relevance
“…Söderman et al reported a 1.5% annual risk of hemorrhage in 53 patients with unruptured DAVFs with CVD. 43 In the same study, this risk increased to 7.4% per year for those with ruptured DAVFs. Strom et al reported a similar annual hemorrhage rate of 1.4% in 17 patients harboring DAVFs with CVD without prior hemorrhage.…”
Section: Comparison Of Davfs With Cvd and Davfs Without Cvdmentioning
confidence: 82%
“…Söderman et al reported a 1.5% annual risk of hemorrhage in 53 patients with unruptured DAVFs with CVD. 43 In the same study, this risk increased to 7.4% per year for those with ruptured DAVFs. Strom et al reported a similar annual hemorrhage rate of 1.4% in 17 patients harboring DAVFs with CVD without prior hemorrhage.…”
Section: Comparison Of Davfs With Cvd and Davfs Without Cvdmentioning
confidence: 82%
“…It has been reported that patients presenting with benign (incidental/pulsatile tinnitus/orbital phenomena) symptoms from cDAVFs with CVD may be at lower annual risk for intracranial hemorrhage (approximately 1.5%) compared with those presenting with aggressive neurologic symptoms. [14][15][16] However, these estimates are based on small patient numbers or short follow-up periods. In the series by Strom et al, 15 1 of 17 patients presenting with benign symptoms from persistent CVD bled 13 years later.…”
Section: Discussionmentioning
confidence: 99%
“…In the series by Strom et al, 15 1 of 17 patients presenting with benign symptoms from persistent CVD bled 13 years later. In another series by Söderman et al, 14 a complicated "time-at-risk" period was calculated by combining the time between symptom onset/nonangiographic diagnosis, the time between diagnostic angiography and treatment, and clinical follow-up. In the cohort of 53 patients who did not present with intracranial hemorrhage, 1 patient bled during a time-at-risk period of 67.1 patient-years, conferring an annual 1.5% risk for intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…22,36,37 Awad et al, 34 in an early meta-analysis, found 203 patients with PT-associated DAVF showing a nonaggressive natural history. Controversy exists as to the rate at which low-grade fistulas convert to aggressive phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists as to the rate at which low-grade fistulas convert to aggressive phenotypes. 23,37 CTA evaluation of cortical venous reflux in the current study was limited for several reasons. The cohort of patients with PT does not, in general, have high-grade fistulas.…”
Section: Discussionmentioning
confidence: 99%